2007
DOI: 10.4161/cc.6.22.4926
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatases: Emerging Regulators of Apoptosis

Abstract: ACKnowLedgeMenTsWe thank Matthew Stuible, Annie Bourdeau and Hannah Heath-Engel for critical reviews of the manuscript and for helpful discussions. We are grateful to Martin Calille for his generous assistance with computer software. We also wish to apologize to authors of studies that were not cited due to space limitation. Maxime Hallé is a recipient of a Rolande and Marcel Gosselin Graduate Studentship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 95 publications
1
21
0
Order By: Relevance
“…Moreover, apoptosis was associated with the activation of caspase-3, -8 and -9, and an increasing Bax:Bcl-2 ratio, followed by release of cytochrome c (17). Caspase-3 is a key molecule in the late stage of apoptosis; caspase-8 normally is activated by extrinsic receptor-mediated pathway; and caspase-9 is activated by intrinsic mitochondrial-mediated pathway (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, apoptosis was associated with the activation of caspase-3, -8 and -9, and an increasing Bax:Bcl-2 ratio, followed by release of cytochrome c (17). Caspase-3 is a key molecule in the late stage of apoptosis; caspase-8 normally is activated by extrinsic receptor-mediated pathway; and caspase-9 is activated by intrinsic mitochondrial-mediated pathway (18).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of the PTP-PEST-PSTPIP-WASP complexes was previously shown to allow PTP-PEST to dephosphorylate WASP (19) and to inhibit WASP-induced actin polymerization (82). It was recently demonstrated that caspase-3-mediated cleavage of PTP-PEST dissociates its phosphatase domain from PSTPIP and was expected to prevent it from dephosphorylating and inhibiting WASP (51,83). Importantly, we show that GP63 mediates the degradation of PTP-PEST during Leishmania infection, which could function to affect parasite-induced actin cytoskeleton remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…PTP1B was originally isolated from human placenta (Charbonneau et al 1989) and is well known to play a major role in the regulation of the immune system, insulin signaling, and cell cycle, as well as in metabolic diseases and various cancers (Tonks 2003;Dubé and Tremblay 2005;Ostman et al 2006). There is also a growing body of evidence that protein tyrosine phosphatases serve as signaling partners for apoptosis (Hallé et al 2007). The human Ptpip51 gene is located on chromosome 15 (15q15.1) and encodes the corresponding full-length protein making up 470 amino acids by 12 exons.…”
mentioning
confidence: 99%